Exploring in vitro effect of silver nanoparticles and Holothuria parva extracts on kinetics and stability of α‐amylase. (28th September 2022) - Edrispour, Zeynab; Homaei, Ahmad
Abstract: Diabetes is a chronic metabolic disorder characterized by elevated blood glucose levels. Major limitations of synthetic drugs, including high cost, efficacy, and adverse side effects, have prompted researchers to seek more effective and low‐cost alternative therapies with fewer adverse effects. Marine life forms are considered the most important sources of biologically active natural products due to their secondary metabolites. In this research, sea cucumber Holothuria parva was collected from coastal areas of Bandar Lengeh, Hormozgan, Iran, and was then subjected to extraction. The results showed that compounds extracted from Holothuria parva had a stimulatory effect on enzyme activity, and in the presence of these compounds, the V max value of the enzyme was increased about two times, while the K m value was reduced. The phosphate buffer form of extracts had the greatest impact on enzyme activity. Upon an increase in the concentration of silver nanoparticles (AgNPs), the α‐amylase activity was inhibited in parallel. Silver nanoparticles exhibited the highest enzyme inhibition with an IC50 of 0.86 mg/ml. Silver nanoparticles showed anti‐α‐amylase activity and had the ability to decrease intestinal glucose uptake in diabetic individuals when prescribed as a novel supplementary medicine. Abstract :